Land suitability for chili on the slopes of Raung Indonesia, towards sustainable agriculture - Basuki, Basuki; Setiawati, Tri Candra; Hermiyanto, Bambang; Budiman, Subhan Arif; Sari, Vega Kartika (Brawijaya University, 2026)
Red chili consumption in Indonesia is recorded to increase by 6.78% or 40.42 thousand tons in 2024 from 1,650.75 thousand tons in 2022, while productivity in 2025 is projected to increase by 6.78%, while chili productivity in 2024 is 1,386.45 thousand tons. 37% of the land area in the Kesambi Sub-watershed is marginal and has potential for horticultural cultivation. The research aims to align land and chili cultivation management on the slopes of Mount Raung, Indonesia, toward sustainable agriculture and national food self-sufficiency. The method used is through data collection, both laboratory data and land biophysical data that are adjusted to match the suitability with plant growth requirements. The results of the study showed that the actual land suitability of red chili plants at 78.87% or 2,558.48 ha was dominated by the marginally suitable class (S3), and 21.13% or 685.58 ha were in the unsuitable category (N), with the most inhibiting factors being erosion hazards, nutrient retention, and air availability. Efforts to improve land quality to produce optimal production for crop achievement through the addition of agricultural fertilizers such as NPK, the provision of organic matter and dolomite, and slope improvement by making “gulud” terraces or providing mulch so that the potential land was achieved to 67.11% or 2,177.01 ha dominated by class S3, 21.13% or 685.58 ha were categorized as unsuitable class (N), and 11.76% or 381.47 ha were categorized as quite suitable class (S2).